Mrs Thatcher's peacock blue sari: ethnic minorities, electoral politics and the Conservative Party, c. 1974–86. Issue 2 (3rd April 2017) - Francis, Matthew
Abstract: The image of Margaret Thatcher appearing on television dressed in a 'peacock blue sari' must seem rather farfetched—and yet, for a brief moment, it appeared a distinct possibility. That such an event seemed plausible reflected the growing recognition among senior Conservatives of the electoral significance of ethnic minority voters. While Conservatives had begun to experiment with measures to appeal to BAME voters as early as 1951, from the mid-1970s formal party structures dedicated to the recruitment and representation of BAME voters began to emerge. In 1976 the Party launched the Anglo Asian Conservative and the National Anglo West Indian Conservative Societies, both of which sought to address poor performance among black and Asian voters. This paper explores the development of Conservative electoral strategies targeting BAME voters in the period after 1951, and reflects on what these strategies reveal about Conservative narratives of the nation in the 1980s.